Dorsal attention network activity during perceptual organization is distinct in schizophrenia and predictive of cognitive disorganization. (4th January 2023) - Keane, Brian P.; Krekelberg, Bart; Mill, Ravi D.; Silverstein, Steven M.; Thompson, Judy L.; Serody, Megan R.; Barch, Deanna M.; Cole, Michael W.
Abstract: Visual shape completion is a canonical perceptual organization process that integrates spatially distributed edge information into unified representations of objects. People with schizophrenia show difficulty in discriminating completed shapes, but the brain networks and functional connections underlying this perceptual difference remain poorly understood. Also unclear is whether brain network differences in schizophrenia occur in related illnesses or vary with illness features transdiagnostically. To address these topics, we scanned (functional magnetic resonance imaging, fMRI) people with schizophrenia, bipolar disorder, or no psychiatric illness during rest and during a task in which they discriminated configurations that formed or failed to form completed shapes (illusory and fragmented condition, respectively). Multivariate pattern differences were identified on the cortical surface using 360 predefined parcels and 12 functional networks composed of such parcels. Brain activity flow mapping was used to evaluate the likely involvement of resting‐state connections for shape completion. Illusory/fragmented task activation differences ('modulations') in the dorsal attention network (DAN) could distinguish people with schizophrenia from the other groups (AUCs > .85) and could transdiagnostically predict cognitive disorganization severity. Activity flow over functional connections from the DAN could predict secondary visual network modulations in each group, except in schizophrenia. The secondary visual network was strongly and similarly modulated in each group. Task modulations were dispersed over more networks in patients compared to controls. In summary, DAN activity during visual perceptual organization is distinct in schizophrenia, symptomatically relevant, and potentially related to improper attention‐related feedback into secondary visual areas. Abstract : People with schizophrenia often show difficulty in discerning visually completed shapes, but little is known about what brain networks may be differentially engaged. Functional MRI revealed that schizophrenia patients exhibited unique activity in the dorsal attention network (DAN) compared to people with bipolar disorder or no psychiatric disorder; such activity could transdiagnostically predict cognitive disorganization severity. A modelling technique further suggested potentially faulty feedback from the DAN to secondary visual regions in schizophrenia.